Drought tolerance traits in genotypes from an upland rice core collection - Terra, Thiago Gledson Rios; Leal, Tarcísio Castro Alves de Barros; Rangel, Paulo Hideo Nakano; Oliveira, Aluísio Borém de (Pesquisa Agropecuaria Brasileira, 2015)
The objective of this work was to evaluate morphophysiological traits related to drought stress tolerance in genotypes from a thematic upland rice core collection, and to identify the most tolerant materials. One hundred upland rice genotypes were evaluated in experiments carried out with or without drought stress. The genotypes tended to increase the number of days to flowering (FLO) and to decrease plant height (ALT) under stress condition, but showed a great variation in behavior. Spikelet sterility (EST) was the most important trait for selection, in both growing conditions, because of its high negative correlation with yield. The number of tillers did not differ among genotypes, under no stress condition, but there was a significant difference under stress condition. The Ligeiro and Canela de Ferro genotypes showed low drought susceptibility indexes (SID), but low yields in both growing conditions; the Catetão, Jatobá, and Arroz do Maranhão materials had high productivity under stress and relatively low SID values. EST, FLO, ALT, and SID are morphophysiological traits related to drought tolerance, and the Catetão, Jatobá, and Arroz do Maranhão genotypes can be a good source of genes for drought tolerance in breeding programs.